NOTES ON THE 6TH SOUTH AFRICAN ARMOURED DIVISION POSTAL UNIT - Ploeger, Jan (Scientia Militaria - South African Journal of Military Studies, 2012)
In February, 1943 the nucleus of the (6th South African Armoured Division was stationed at Premier Mine, Transvaal. From then onwards units which eventuallv werl to become part of the Division, joined this nucleus from various parts of the country.